PENENTUAN JURUSAN PADA PROSES PENERIMAAN MAHASISWA DENGAN PENDEKATAN LOGIKA FUZZY: PENENTUAN JURUSAN PADA PROSES PENERIMAAN MAHASISWA DENGAN PENDEKATAN LOGIKA FUZZY - Ari Purno Wahyu; Umi Hayati (Universitas Widyatama, 2021)
Choosing a major is not an easy matter. There are many factors that must be taken into account and carefully thought out so that in choosing a major, it will cause big losses. There are many ways to determine the selection of majors, one of which is by using fuzzy logic. Determination of majors is determined from the results of the selection test in the academic field with the subjects of Mathematics, English and Computer Knowledge. With the aim of recommending the selection of the right major according to academic abilities and improving quality. By using the fuzzy inference model Mamdani max-min method. The system simulation was tried using the MATLAB Fuzzy Toolbox software. The system design is carried out in several stages, namely: (1) formation of fuzzy sets, (2) formation of rules, (3) determination of the composition of rules, and (4) confirmation (defuzzification). Defuzzification is carried out using the Composite Moment method, with the types of membership functions used are mf-triangular, mf-trapezoid and mf-gaussian. From the results of the tests carried out, it shows that the mf-triangular and mf-trapezoid membership function types produce almost the same level of accuracy. While the membership function type mf-gaussian produces a high level of accuracy for mathematics by 87.50%, English 100% and computer knowledge 81.58%.